Liberté - Angelo, Gretchen (Open textbook library., 2017)
This French book is aimed at a first-year college student. Its features include: Each chapter is built around communicative strategies. Clearly defined objectives in communi- cation, culture, and grammar are given at the start of each chapter, and summary exercises at the end allow students to measure their mastery of these objectives. The exercises in the in-class (A) sections are composed mainly of guided practice and extension activities, along with occasional comprehension checks and comprehensible input. Some further activities are indicated in the instructor's marginal notes. The teacher can provide teacher- directed “setting-the-stage” activities, comprehension checks, and further comprehensible input before beginning each section. Many models are provided to the students to give them a secure context in which to practice their vocabulary before they are asked to produce independent language. The grammar included is explained in a more narrative form and in more detail than is typical for first-year textbooks. The grammar (B) sections should be read by the students outside of class before the communicative activities requiring those grammar points are done in class. By providing more explicit grammatical detail than is usual in a first-year book, the author hopes to stimulate students to reflect on the grammar of their own language as well as of French, helping students to become aware that their study of French is not just about mastery of a new language and culture, but about a more critical view of their own. The amount of grammar is less than is typically contained in a first-year text. The grammar included has been chosen to meet the needs of the communicative goals of each chapter, and these have been selected based on what a student ranking intermediate-low to -mid on the ACTFL oral proficiency scale should be able to accomplish. The grammatical concepts included in this book focus on those that will be needed for the sentences and questions that a typical low-intermediate speaker can form, and those are emphasized repeatedly. The book implicitly and explicitly recycles material from previous chapters on a regular basis, so that students can see their learning as a continual progression rather than as a rush from one grammar point to the next. The book is ideally used in a classroom with internet and projection capabilities; the PDF version of the book contains hyperlinks to video and audio-based activities as well as navigational links to referenced exercises within the text itself.